Dazzling damselfish: investigating motion dazzle as a defence strategy in humbug damselfish (Dascyllus aruanus) - Louise Tosetto; Nathan S. Hart; Laura A. Ryan (PeerJ, 2024)
Many animals possess high-contrast body patterns. When moving, these patterns may create confusing or conflicting visual cues that affect a predator’s ability to visually target or capture them, a phenomenon called motion dazzle. The dazzle patterns may generate different forms of optical illusion that can mislead observers about the shape, speed, trajectory and range of the animal. Moreover, it is possible that the disruptive visual effects of the high contrast body patterns can be enhanced when moving against a high contrast background. In this study, we used the humbug damselfish (Dascyllus aruanus) to model the apparent motion cues of its high contrast body stripes against high contrast background gratings of different widths and orientations, from the perspective of a predator. We found with higher frequency gratings, when the background is indiscriminable to a viewer, that the humbugs may rely on the confusing motion cues created by internal stripes. With lower frequency gratings, where the background is likely perceivable by a viewer, the humbugs can rely more on confusing motion cues induced by disruption of edges from both the background and body patterning. We also assessed whether humbugs altered their behaviour in response to different backgrounds. Humbugs remained closer and moved less overall in response to backgrounds with a spatial structure similar to their own striped body pattern, possibly to stay camouflaged against the background and thus avoid revealing themselves to potential predators. At backgrounds with higher frequency gratings, humbugs moved more which may represent a greater reliance on the internal contrast of the fish’s striped body pattern to generate motion dazzle. It is possible that the humbug stripes provide multiple protective strategies depending on the context and that the fish may alter their behaviour depending on the background to maximise their protection.